A patient care report of a young crossbreed dog with a patent ductus arteriosus. (2nd April 2022) - Murphy, Emma
Abstract : Patent ductus arteriosus (PDA) is one of the most common congenital diseases seen in dogs, which usually will result in heart failure and death if left untreated. Veterinary nurses play a key role in the care of these patients through all stages of diagnosis and treatment, and understanding the disease process allows nurses to provide a higher standard of care through preparation and understanding of likely effects and outcome of disease on patients. This case report looks at the diagnosis, treatment and nursing care provided to a young crossbreed dog diagnosed with a PDA following auscultation of a loud, continuous heart murmur.